Pengaruh Pandemi Covid-19 dan Metode Pembelajaran Jarak Jauh Terhadap Persepsi Kualitas Lulusan Pendidikan Tinggi Vokasi Penerbangan - Lina Rosmayanti; Dedy Fachrudin; Afrizal (Politeknik Penerbangan Indonesia Curug, 2021)
Since the end of 2019, the Covid-19 pandemic has spread to various countries rapidly and has affected every aspect of life in the world community. The order of life has changed drastically, including the world of education. Since the issuance of a circular instructing each educational institution to organize distance learning, each student follows the learning process from their respective homes through various media. With all the existing limitations, educational institutions, especially aviation vocational higher education, are still expected to be able to maintain the quality of education and graduates. Vocational higher education, where the majority of the material is practice, certainly experiences obstacles because students cannot carry out practices. This has the potential to decrease the perception of the quality of graduates. This is what encourages the author to conduct this research. This research uses quantitative methods, and a questionnaire as an instrument of data collection. Finally, this study gives the results that the Covid-19 pandemic and distance learning methods have an influence or contribution to the perception of the quality of aviation vocational higher education graduates with the strength of the relationship between variables is weak